PENGEMBANGAN DIGITAL SMART BOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SEKOLAH DASAR - Indah Fitrihani; Yuyu Yuhana; Aan Subhan Pamungkas; Indhira Asih V.Y (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This research is motivated by the less than optimal use of digital learning media. This study uses the Research and Development (R&D) method which aims to produce digital smart book textbooks, test the feasibility of digital smart books and determine the improvement of higher order thinking in 5th grade students of SDIT Laa Tahzan through the development of digital smart books. The development of this product is guided by the Sugiyono model which is modified into six steps including problem analysis, data collection, product design, product validation, product revision, to product testing. The digital smart book feasibility test is carried out by material, media and language experts. Validation from the three experts showed the results of "Fair" to "Very Eligible". The results of student responses to digital smart books get a percentage of 96.66% and are included in the "Very Good" category. This is reinforced by obtaining an N-Gain value of 0.506 which is included in the "Medium" criteria. Based on the results of the study, it can be concluded that digital smart books to improve the higher-order thinking skills of elementary school students have been successfully developed, suitable for use in learning, the responses given by students are supported by increasing higher-order thinking skills in students with the use of digital smart books in learning.